Indigenous Lands inhibit mining-induced deforestation in the Brazilian Amazon - Ribas, Luiz Guilherme dos Santos [UNESP]; Galetti, Mauro [UNESP] (Elsevier, 2025)
Indigenous Lands (ILs) have been recognized as valuable tools for Amazon conservation. Originally established to protect indigenous rights and culture, they have unintentionally become essential for environmental conservation. ILs cover approximately 23 % of the Brazilian Legal Amazon and face significant threats, including from mining activities. Proposed legislative changes aim to facilitate mineral exploration within ILs, leading to an increase in mining claims and illegal mining activities. This study assesses the impact of ILs in the Brazilian Legal Amazon on mining-induced deforestation by comparing it to a counterfactual scenario in the absence of ILs. The results indicate that ILs are effective in avoiding mining-induced deforestation, preventing the accumulated deforestation of approximately 25 million hectares between 2004 and 2019. This corresponds to 20 % of all ILs’ territories and 4.7 % of the Brazilian Legal Amazon extension. Although their effectiveness has declined over the years, this underscores the importance of ILs in protecting nature and indigenous communities. The results also suggest that the individual impacts of ILs on mining-induced deforestation vary across the Brazilian Amazon. These individual variations highlight challenges in which decision-makers should strengthen governance, enhance enforcement, and implement targeted policies to safeguard the Amazon rainforest and indigenous rights.
Keywords: Amazon rainforest; Causal inference; Conservation intervention; Impact evaluation; Indigenous rights; Matching methods